Marine Actinobacteria amo.128 Isolated from Seribu Island: Antibacterial, Antibiofilm and Molecular Docking as Quorum Sensing Inhibitors - Cahyanto, Heru Agus; Sunaryanto, Rofiq; Damayanti, Ema; Mustofa (HAYATI Journal of Biosciences, 2025)
The prevalence of antibiotic-resistant bacteria is increasing every year in Indonesia. This resistance occurs in several antimicrobial categories. A contributing factor to microbial resistance is the capacity of microbes to develop biofilms. Amo.128 is an actinomycete from the Laboratory Biotechnology, BRIN Serpong collection, which is expected to have both antimicrobial and antibiofilm activity. This study aimed to identify amo.128 macroscopically, microscopically, and molecularly; to determine the antibacterial and antibiofilm activity; to identify secondary metabolites; and to understand the mechanism of quorum sensing inhibition by in silico with proteins targeting SdiA and AgrA. Based on macroscopic and microscopic observations, the amo.128 isolate belongs to the genus Streptomyces. Phylogenetic analysis of the amo.128 isolate is 100% similar to Streptomyces parvus strain NBRC 14599. The amo.128 metabolite contains several compounds, including N-acetyltyramine, cyclophenylalanylprolyl/cFP, and the pyrrole-pyrazine group. The MIC/MBC/MIC50 value of the amo.128 metabolite against Staphylococcus aureus is 25/50/28.48 ppm, while for Escherichia coli it is 100/200/49.38 ppm. The amo.128 metabolite reduced biofilms formed by S. aureus and E. coli with BRC50 values of 62.07 ppm and 60.44 ppm, respectively. The amo.128 metabolite compound, cyclophenylalanylprolyl/cFP, has potential activity as a quorum-sensing inhibitor.